2020
DOI: 10.1371/journal.pone.0227198
|View full text |Cite
|
Sign up to set email alerts
|

Usability assessment of seven HIV self-test devices conducted with lay-users in Johannesburg, South Africa

Abstract: IntroductionThe first 90 of the 90-90-90 initiative introduced by the World Health Organization(WHO) in 2015 requires 90% of people with HIV be aware of their status by 2020. In South Africa, conventional facility-based testing had reached 84.9% in 2018; innovative new methods, like HIV self-testing(HIVST) may close the testing gap. This study aimed to determine the usability of seven HIVST kits among untrained South Africans. MethodsThis cross-sectional study of 1400 adults in Johannesburg evaluated the usabi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
45
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(58 citation statements)
references
References 20 publications
(26 reference statements)
6
45
1
Order By: Relevance
“…Errors stemming from the IFUs have been well documented in a number of HIVST studies, including ones from South Africa. 38 , 39 , 40 Suggestions like clarifying the instructions, incorporating video or voice notes, and offering additional languages should all be taken into consideration, especially as more HIVSTs, each with specific IFUs, become available to the market. Some of these suggestions have already been implemented by other platforms, as the HIVSmart TM app is already available in both of Canada’s national languages, and provides supplemental video content.…”
Section: Discussionmentioning
confidence: 99%
“…Errors stemming from the IFUs have been well documented in a number of HIVST studies, including ones from South Africa. 38 , 39 , 40 Suggestions like clarifying the instructions, incorporating video or voice notes, and offering additional languages should all be taken into consideration, especially as more HIVSTs, each with specific IFUs, become available to the market. Some of these suggestions have already been implemented by other platforms, as the HIVSmart TM app is already available in both of Canada’s national languages, and provides supplemental video content.…”
Section: Discussionmentioning
confidence: 99%
“…Metrics to evaluate usability and acceptability were based on the HIV self-testing literature (5,6,8) and were measured as the percentage of participants responding to specific closed questions in the online survey. The questionnaire used is available as an online supplement (Supplement, S2).…”
Section: Study Outcomesmentioning
confidence: 99%
“…There are many advantages in terms of uptake, cost, patient activation and scale (4,6), but also potential disadvantages in relation to validity, usability and practicality which should be explored (6,7). Usability research on HIV selftesting has generally found good acceptability, the devices easy to use and high validity in interpretation of self-reported test results (7)(8)(9). However, these HIV test kits were designed for selfsampling and self-testing and went through several iterations before designs were appropriate for home use and therefore the same levels of acceptability and usability for home-based self-testing for SARS-CoV-2 antibody using LFIAs cannot be assumed.…”
Section: Introductionmentioning
confidence: 99%
“…An exit interview guide was developed to qualitatively assess specific facilitators and barriers for syphilis self-testing. Participants also completed a survey to establish quantitative usability of the test, adapted from a HIVST usability index used in South Africa (20). Qualitative data was analysed following the Rapid Assessment Procedures (RAP), a set of methodologies designed for rapid assessment of health-seeking behaviour (21).…”
Section: Methodsmentioning
confidence: 99%